(untitled) (Journal of the College of Basic Education, 2025)
This study examines e-learning as a modern tool that integrates a variety of technological means, ranging from simple tools to advanced technologies, aimed at facilitating the processes of teaching and learning. E-learning offers flexible educational opportunities that accommodate students’ diverse abilities and learning speeds, making it an effective method that enhances the learning experience with excitement and engagement. It also encourages greater student involvement, accelerates their comprehension, reduces the time required for learning, and significantly minimizes individual differences among learners.The current research focuses on identifying the challenges associated with utilizing e-learning in teaching Arabic language courses, from the perspective of faculty members. The study aims to explore the nature of these challenges through a field study targeting faculty members in the Arabic language departments at the Colleges of Education in the University of Babylon and Al-Mustansiriyah University during the academic year 2020–2021. The research population consisted of 30 faculty members. The researcher employed a questionnaire comprising 30 items designed to achieve the study’s objectives. The validity and reliability of the research instrument were confirmed prior to its application to the study sample. Statistical analysis of the results revealed that 21 out of the 30 items included in the study were identified as challenges faced by faculty members when using e-learning to teach Arabic language courses.